Electrode for lithium battery having improved interfacial stability and mechanical stability and method of manufacturing thereof and lithium battery including the same
A TiO2 coating on silicon particles using a sol-gel process addresses the structural instability of all-solid-state batteries by blocking direct contact with sulfide-based electrolytes, enhancing interfacial stability and mechanical integrity while maintaining high energy density and output.
Patent Information
- Application Number
- KR1020260122331
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2046-07-03
AI Technical Summary
Conventional lithium-ion batteries face issues with electrolyte leakage, flammability, and structural instability due to silicon's volume changes, which degrade interfacial stability and mechanical integrity in all-solid-state batteries, particularly with sulfide-based solid electrolytes.
A TiO2 protective coating layer is applied to silicon particles using a sol-gel process to form a continuous film, blocking direct contact with sulfide-based solid electrolytes and mitigating volume expansion, thereby enhancing interfacial and mechanical stability.
The TiO2 coating suppresses interfacial reactions, maintains stable contact, improves cycle life, and ensures high energy density and output characteristics by reducing interfacial resistance and structural degradation.
Smart Images

Figure 112026081086780-PAT00004_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to an electrode with improved interfacial stability and mechanical stability, a method for manufacturing the same, and a lithium battery thereof. More specifically, by introducing a TiO2 protective coating layer onto the surface of a micro silicon active material using a sol-gel process, the TiO2 protective coating layer is uniformly formed on the surface of silicon particles to suppress volume expansion and ensure structural stability, and the invention relates to an electrode with improved interfacial stability and mechanical stability, a method for manufacturing the same, and a lithium battery thereof, wherein a high-density electrode can be formed based on a high tap density through a silicon anode made of micro silicon. Background Technology
[0003] With the recent expansion of electric vehicles (EVs), energy storage systems (ESS), drones, robots, and various portable electronic devices, the development of next-generation secondary batteries that simultaneously satisfy high energy density and excellent safety is actively underway. In particular, conventional lithium-ion batteries using liquid electrolytes have continuously raised issues such as electrolyte leakage, fire and explosion risks due to flammability, and stability limitations in high-voltage environments.
[0004] As a solution to these problems, all-solid-state batteries, which use solid electrolytes instead of liquid electrolytes, are attracting attention as next-generation energy storage devices. By using non-flammable solid electrolytes, all-solid-state batteries can significantly improve safety and enable high energy density, while also offering advantages for battery miniaturization and high power output.
[0005] In particular, sulfide-based solid electrolytes exhibit higher lithium ion conductivity compared to oxide-based solid electrolytes and have excellent adhesion to electrodes, so they are being actively researched as solid electrolytes for all-solid-state batteries.
[0007] Meanwhile, silicon is attracting attention as an anode active material to further improve the energy density of all-solid-state batteries. Silicon has a very high theoretical capacity of approximately 3,500 mAh / g, which offers the advantage of enabling much higher energy density than graphite-based anode active materials, which have a theoretical capacity of approximately 372 mAh / g. Furthermore, due to its abundant resources and relatively low cost, silicon holds high potential as a next-generation anode active material.
[0008] However, silicon undergoes repeated volume changes, expanding by more than 300% as it alloys with lithium ions during the charging process and contracting again during the discharging process. This repeated expansion and contraction causes cracking and pulverization of silicon particles, structural collapse of the active material layer, and a decrease in electrical contact within the electrode.
[0009] In particular, in all-solid-state batteries, unlike liquid electrolytes, solid electrolytes have difficulty absorbing deformation; therefore, volume changes in silicon cause problems that further exacerbate interface cracking, delamination, and contact loss between the solid electrolyte and the anode.
[0010] Furthermore, while sulfide-based solid electrolytes provide high lithium ion conductivity, direct contact with silicon active materials can lead to interfacial side reactions during charging and discharging, which can accelerate the decomposition of the sulfide-based solid electrolyte. During this process, electrochemically unstable decomposition products are formed at the interface, causing a continuous increase in interface resistance.
[0011] This increase in interfacial resistance hinders the movement of lithium ions, which not only degrades output characteristics and rate capability but also causes a decrease in capacity retention and cycle life during long-term charge and discharge processes.
[0012] Conventionally, carbon coating, metal oxide coating, metal phosphate coating, and various surface modification technologies have been proposed to solve these problems.
[0013] However, carbon coatings have the problem of insufficient chemical stability with sulfide-based solid electrolytes, and some metal oxide coatings have limitations in that the coating layer is non-uniform or formed only partially in the form of particles, failing to effectively protect the entire silicon active material. In addition, if the coating layer is excessively thick, the lithium ion mobility resistance increases, which can degrade electrochemical performance; conversely, if the coating layer is too thin or discontinuous, there is a problem in that it fails to sufficiently block direct contact between the silicon active material and the sulfide-based solid electrolyte.
[0014] Therefore, there is a need to develop a new protective coating technology that can effectively suppress direct interfacial reactions with sulfide-based solid electrolytes while maintaining the high capacity characteristics of silicon active materials, and stably maintain interfacial contact even with repeated volume changes of silicon occurring during the charge-discharge process.
[0015] A relevant prior art document is Korean Published Patent Application No. 10-2025-0021820 (published on February 14, 2025), which describes a negative electrode material for a secondary battery comprising a polymer protective layer and a method for manufacturing the same. The problem to be solved
[0017] The objective of the present invention is to provide an electrode with improved interfacial stability and mechanical stability, a method for manufacturing the same, and a lithium battery thereof, wherein a TiO2 protective coating layer is uniformly formed on the surface of silicon particles by introducing a TiO2 protective coating layer on the surface of a micro silicon active material using a sol-gel process, thereby suppressing volume expansion and ensuring structural stability, and enabling the formation of a high-density electrode based on a high tap density through a silicon anode made of micro silicon. means of solving the problem
[0019] An electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention for achieving the above objective comprises: a negative electrode current collector; and a negative electrode active material layer formed on the negative electrode current collector; wherein the negative electrode active material layer comprises: a silicon active material including micro silicon; and a TiO2 protective coating layer formed to cover the surface of the silicon active material; wherein the TiO2 protective coating layer is formed to cover the surface of the silicon active material in the form of a continuous film and is disposed between the silicon active material and a sulfide-based solid electrolyte.
[0020] The above micro silicon has an average diameter of 1 to 20 μm.
[0021] The above TiO2 protective coating layer has an average film thickness of 1 to 10 nm.
[0022] It is more preferable that the above TiO2 protective coating layer has an average film thickness of 3 to 5 nm.
[0023] The above TiO2 protective coating layer is formed by a sol-gel process.
[0024] The above TiO2 protective coating layer covers more than 80% of the surface area of the silicon active material.
[0025] The above TiO2 protective coating layer blocks direct contact with the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and reducing the increase in interfacial resistance.
[0027] A lithium battery with improved interfacial stability and mechanical stability according to an embodiment of the present invention for achieving the above objective comprises: a positive electrode; a negative electrode disposed opposite to the positive electrode; and a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode; wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, and the negative electrode active material layer comprises a silicon active material including micro silicon and a TiO2 protective coating layer formed to cover the surface of the silicon active material, wherein the TiO2 protective coating layer is formed to cover the surface of the silicon active material in the form of a continuous film and is disposed between the silicon active material and the sulfide-based solid electrolyte.
[0028] The above micro silicon has an average diameter of 1 to 20 μm.
[0029] It is more preferable that the above TiO2 protective coating layer has an average film thickness of 1 to 10 nm.
[0030] The above TiO2 protective coating layer has an average film thickness of 3 to 5 nm.
[0031] The above TiO2 protective coating layer is formed by a sol-gel process.
[0032] The above TiO2 protective coating layer covers more than 80% of the surface area of the silicon active material.
[0033] The above TiO2 protective coating layer blocks direct contact with the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and reducing the increase in interfacial resistance.
[0035] A method for manufacturing an electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention for achieving the above objective comprises: (a) a step of forming a TiO2 protective coating layer to cover the surface of a silicon active material containing micro silicon in the form of a continuous film by a sol-gel process; (b) a step of forming a negative electrode slurry composition by mixing the silicon active material with the formed TiO2 protective coating layer, a conductive material, and a binder with a solvent; (c) a step of forming a negative electrode slurry coating layer by coating the negative electrode slurry composition onto a negative electrode current collector; and (d) a step of forming a negative electrode active material layer by drying the negative electrode current collector on which the negative electrode slurry coating layer is formed.
[0036] The above step (a) comprises: (a-1) dispersing the micro silicon in a dispersion solution containing anhydrous ethanol and an aqueous ammonia solution; (a-2) adding a titanium alkoxide precursor dropwise to the dispersion solution to induce hydrolysis and condensation reactions; (a-3) stirring after the hydrolysis and condensation reactions to form a TiO₂ protective coating layer on the surface of the micro silicon, followed by centrifugation, washing, and drying; and (a-4) heat-treating the dried product.
[0037] In step (a-2) above, the titanium alkoxide precursor is preferably titanium tetraisopropoxide (TTIP).
[0038] In step (a-3) above, the TiO2 protective coating layer has an average film thickness of 1 to 10 nm.
[0039] It is more preferable that the above TiO2 protective coating layer has an average film thickness of 3 to 5 nm.
[0040] In step (a-3) above, the TiO2 protective coating layer covers an area of at least 80% of the surface of the silicon active material.
[0041] In step (a-4) above, the heat treatment is carried out at 600 to 700°C for 1 to 5 hours under inert gas atmosphere conditions.
[0042] In step (d) above, the drying comprises: a step of primary drying for 5 to 30 minutes at a temperature of 70 to 90°C under atmospheric pressure or reduced pressure; and a step of secondary drying the primary dried product for 1 to 6 hours at a temperature of 75 to 95°C under vacuum atmosphere. Effects of the invention
[0044] The present invention can provide a stable interfacial protection layer between a silicon active material and a sulfide-based solid electrolyte by forming a continuous film-type TiO2 protective coating layer on the surface of a silicon active material containing micro-silicon. Accordingly, the present invention can effectively block or reduce direct contact between the silicon active material and the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and side interfacial reactions, and significantly improve chemical stability at the interface.
[0045] Furthermore, the present invention allows the TiO2 protective coating layer to continuously cover the surface of the silicon active material, thereby effectively relieving stress caused by the repeated volume expansion and contraction of the silicon active material during the charging and discharging process. Accordingly, the present invention can improve the mechanical stability of the electrode by suppressing cracking of the silicon active material, collapse of the active material layer, interfacial delamination, and contact loss, and can maintain stable interfacial contact even when charging and discharging are repeated for a long period.
[0046] In addition, the present invention can improve charge / discharge efficiency and secure excellent rate capability by effectively suppressing the increase in interface resistance between the silicon active material and the sulfide-based solid electrolyte and stably maintaining the lithium ion migration path through a TiO2 protective coating layer. Furthermore, it can improve long-term charge / discharge cycle life and capacity retention by reducing electrochemical degradation of the interface.
[0047] In addition, the present invention can minimize the resistance to lithium ion movement while ensuring sufficient protection for the silicon active material by strictly controlling the average film thickness of the TiO2 protective coating layer to 1 to 10 nm. Therefore, it is possible to simultaneously satisfy the interfacial protection effect and electrochemical performance, and simultaneously realize high energy density and excellent output characteristics.
[0048] In addition, the present invention allows for the TiO2 protective coating layer to uniformly cover more than 80% of the surface area of the silicon active material, thereby effectively reducing local interfacial reactions and ensuring uniform interfacial characteristics across the entire electrode. Accordingly, performance variations between cells can be reduced, and stable battery characteristics can be maintained over a long period.
[0049] Furthermore, since the present invention forms a TiO2 protective coating layer using a sol-gel process, a uniform and dense protective coating layer can be formed on the surface of micro-silicon without complex vacuum deposition equipment. Accordingly, the manufacturing process offers excellent reproducibility and reduces process costs, and can be easily applied to large-area processes and mass production.
[0050] Accordingly, the present invention can simultaneously improve interfacial stability, mechanical stability, long-term charge / discharge cycle characteristics, capacity retention rate, rate capability characteristics, and battery reliability, and can be effectively applied to electric vehicles (EVs), energy storage systems (ESS), and various next-generation all-solid-state battery fields requiring high energy density and high safety. Brief explanation of the drawing
[0052] FIG. 1 is a cross-sectional view showing a lithium battery with improved interfacial stability and mechanical stability according to an embodiment of the present invention. FIG. 2 is a process flowchart illustrating a method for manufacturing an electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention. Figure 3 is an SEM image showing the Si@TiO2 composite active material prepared according to Example 1. Figures 4 and 5 are photographs showing the results of ESD mapping analysis for the Si@TiO2 composite active material prepared according to Example 1. Figure 6 is a graph showing the XRD analysis results for the Si@TiO2 composite active material prepared according to Example 1 and the micro silicon active material prepared according to Comparative Example 1. FIG. 7 is a graph showing the measurement results of charge transfer resistance before cycling for batteries prepared according to Example 1 and Comparative Example 1. FIG. 8 is a graph showing the measurement results of charge transfer resistance after cycling for batteries prepared according to Example 1 and Comparative Example 1. FIG. 9 is a graph showing the results of the charge-discharge cycle characteristic evaluation for batteries prepared according to Example 1 and Comparative Example 1. Specific details for implementing the invention
[0053] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0054] The electrode with improved interfacial stability and mechanical stability according to a preferred embodiment of the present invention, its manufacturing method, and its lithium battery are described in detail below with reference to the attached drawings.
[0056] An electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention may include a negative electrode current collector and a negative electrode active material layer.
[0058] The negative current collector may be a conductive substrate for supporting the negative active material layer and collecting electrons. For example, the negative current collector may be made of copper (Cu), nickel (Ni), stainless steel, nickel-plated copper, a copper alloy, or a combination thereof. Preferably, the negative current collector may be a copper foil, but is not limited thereto.
[0060] The negative electrode active material layer may be formed on at least one surface of the negative electrode current collector. The negative electrode active material layer may include a silicon active material comprising micro silicon and a TiO2 protective coating layer formed to cover the surface of the silicon active material.
[0061] Silicon active materials serve as negative electrode active materials for all-solid-state batteries and are capable of performing alloying and dealloying reactions with lithium ions. Since silicon possesses a higher theoretical capacity compared to graphite-based active materials, it can improve the energy density of all-solid-state batteries. However, silicon may undergo repeated volume changes, such as significant volume expansion due to lithium ion insertion during charging and subsequent contraction during discharging. These volume changes can lead to cracking of silicon particles, structural collapse of the active material layer, interfacial delamination between the negative electrode active material layer and the sulfide-based solid electrolyte, and an increase in interfacial resistance.
[0062] In the present invention, micro silicon can be used as a silicon active material. Micro silicon has an average diameter (D 50 It is preferable to use microsilicon with a diameter of 1 to 20 µm. If the average diameter of the microsilicon is less than 1 µm, the specific surface area of the particles increases excessively, which increases the possibility of adverse reactions with sulfide-based solid electrolytes and raises concerns about particle aggregation during dispersion and coating processes. Conversely, if the average diameter of the microsilicon exceeds 20 µm, stresses generated inside and on the surface of the particles increase during the charge-discharge process, raising concerns about cracking, fragmentation, and electrode structural deterioration of the silicon particles. Therefore, by using microsilicon with an average diameter within the above range, high capacitance characteristics and electrode structural stability can be secured in balance.
[0063] A TiO2 protective coating layer is formed to cover the surface of a silicon active material. Specifically, the TiO2 protective coating layer may be formed to cover the surface of the silicon active material in the form of a continuous film. Here, "continuous film form" may mean that the TiO2 is not merely attached discontinuously in the form of particles, but forms a coating film that is continuously connected along the surface of the silicon active material. However, the continuous film form in the present invention is not limited to cases where the entire surface of the silicon active material is completely covered 100%, and includes a coating film having a degree of continuity sufficient to substantially reduce direct contact between the silicon active material and the sulfide-based solid electrolyte.
[0064] A TiO2 protective coating layer can be placed between the silicon active material and the sulfide-based solid electrolyte. That is, when the all-solid-state battery is assembled, the TiO2 protective coating layer is positioned between the surface of the silicon active material and the sulfide-based solid electrolyte to function as a protective film. Accordingly, direct contact between the silicon active material and the sulfide-based solid electrolyte can be blocked or reduced, and the decomposition of the sulfide-based solid electrolyte and interfacial side reactions that may occur during the charging and discharging process can be suppressed.
[0065] Generally, sulfide-based solid electrolytes have the advantage of exhibiting high lithium ion conductivity; however, when in direct contact with silicon-based negative electrode active materials, interfacial reactions can occur during the charge-discharge process, leading to the formation of decomposition products. These decomposition products can increase interfacial resistance, impede lithium ion migration pathways, and degrade long-term cycle performance.
[0066] Accordingly, in the present invention, a TiO2 protective coating layer is placed between the silicon active material and the sulfide-based solid electrolyte, thereby suppressing direct interfacial reactions between the sulfide-based solid electrolyte and the silicon active material. In addition, the TiO2 protective coating layer can mitigate interfacial degradation caused by the repeated expansion and contraction of the silicon active material.
[0067] TiO2 has excellent chemical stability and can act as a relatively stable oxide-based protective layer at the interface with sulfide-based solid electrolytes. Accordingly, it can effectively suppress the decomposition of sulfide-based solid electrolytes and interfacial side reactions that occur due to direct contact between the silicon active material and the sulfide-based solid electrolyte during the charging and discharging process of all-solid-state batteries.
[0068] Furthermore, when TiO2 is formed as a continuous film on the surface of a silicon active material, it can function as a buffer protective layer that mitigates interfacial cracking, delamination, and contact loss caused by the repeated volume expansion and contraction of silicon. Therefore, it can stably maintain interfacial contact during the charging and discharging process of an all-solid-state battery and suppress the increase in interfacial resistance.
[0069] Therefore, even if the silicon active material expands during the charging and discharging process, the TiO2 protective coating layer acts as a protective film formed on the surface of the silicon active material to stabilize interfacial contact between the silicon active material and the sulfide-based solid electrolyte, and can reduce interfacial cracking, interfacial delamination, and local contact loss. Accordingly, the interfacial stability and mechanical stability of the all-solid-state battery can be improved.
[0070] To this end, it is preferable that the average film thickness of the TiO2 protective coating layer be 1 to 10 nm. If the average film thickness of the TiO2 protective coating layer is less than 1 nm, it is difficult to sufficiently protect the surface of the silicon active material, and there is a concern that direct interfacial reactions between the silicon active material and the sulfide-based solid electrolyte may not be sufficiently suppressed. Conversely, if the average film thickness of the TiO2 protective coating layer exceeds 10 nm, the TiO2 protective coating layer acts as a resistance layer for lithium ion movement, increasing the interfacial resistance of the electrode and potentially degrading the rate capability and output characteristics.
[0071] More preferably, the TiO2 protective coating layer may have an average film thickness of 3 to 5 nm. Within this range, direct contact between the silicon active material and the sulfide-based solid electrolyte can be effectively blocked while minimizing the increase in lithium ion mobility resistance. Therefore, a TiO2 protective coating layer having an average film thickness of 3 to 5 nm is particularly desirable in terms of the balance of interfacial stability, mechanical stability, and electrochemical properties.
[0072] The TiO2 protective coating layer can cover more than 80% of the surface area of the silicon active material. Here, the coverage area can be confirmed using, for example, transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), or X-ray photoelectron spectroscopy (XPS). If the coverage area of the TiO2 protective coating layer is less than 80% of the surface area of the silicon active material, the exposed area of the silicon active material increases, leading to an increase in the direct contact area with the sulfide-based solid electrolyte, and it may be difficult to sufficiently suppress interfacial side reactions and an increase in interfacial resistance. Conversely, if the TiO2 protective coating layer covers more than 80% of the surface area of the silicon active material, the direct contact area between the silicon active material and the sulfide-based solid electrolyte can be effectively reduced, thereby improving interfacial stability.
[0073] This TiO2 protective coating layer can be formed via a sol-gel process. The sol-gel process utilizes the hydrolysis and condensation reactions of titanium alkoxide precursors to form a uniform TiO2 protective coating layer on the surface of a silicon active material. In particular, when using the sol-gel process, the TiO2 precursor can be uniformly distributed along the surface of micro-silicon particles, and a dense and continuous TiO2 protective coating layer can be formed through a subsequent heat treatment process.
[0074] Since the TiO2 protective coating layer is formed by a sol-gel process, the surface of the silicon active material can be coated in the form of a continuous film, unlike simple mechanical mixing or discontinuous particle attachment methods. Accordingly, the exposed surface area of the silicon active material is reduced, direct contact with the sulfide-based solid electrolyte can be suppressed, and the increase in interfacial resistance during the charging and discharging process of the all-solid-state battery can be reduced.
[0075] Furthermore, TiO2 exhibits excellent chemical stability and can act as a relatively stable protective layer at the interface with sulfide-based solid electrolytes. Therefore, the TiO2 protective coating layer can suppress the decomposition of sulfide-based solid electrolytes during the charge-discharge process, mitigate interfacial degradation caused by volume changes of the silicon active material, and reduce the increase in interfacial resistance.
[0076] In this way, the electrode according to the present invention can block or reduce direct contact between the silicon active material and the sulfide-based solid electrolyte by forming a continuous film-shaped TiO2 protective coating layer on the surface of the silicon active material containing micro silicon. Accordingly, decomposition of the sulfide-based solid electrolyte and interfacial side reactions are suppressed, interfacial cracking and delamination caused by volume changes of the silicon active material during the charge-discharge process are mitigated, and interfacial stability, mechanical stability, long-term cycle characteristics, and rate capability characteristics of the all-solid-state battery can be improved.
[0078] In addition, in the present invention, the negative electrode active material layer may comprise 80 to 95 weight% of a silicon active material having a TiO2 protective coating layer formed thereon, 0.1 to 10 weight% of a conductive material, and 1 to 10 weight% of a binder.
[0079] If the amount of silicon active material with a TiO2 protective coating layer is less than 80 weight%, the ratio of active material in the electrode is low, and the effect of improving the capacity and energy density of the battery may not be sufficiently expressed. Conversely, if the amount of silicon active material with a TiO2 protective coating layer exceeds 95 weight%, the relative content of conductive material and binder becomes insufficient, and there is a risk that the electrical conductivity, binding strength, and structural stability of the electrode will be reduced.
[0080] A conductive material is added to form a conductive network within the negative electrode active material layer to improve electrical contact between active materials and to reduce polarization of the electrode during the charging and discharging process, thereby ensuring excellent output characteristics and high rate characteristics. The conductive material may include one or more selected from Super-P, Ketjen black, Denka black, carbon black, carbon nanotubes (CNT), multi-walled carbon nanotubes (MWCNT), carbon nanofibers (CNF), and vapor grown carbon fibers (VGCF).
[0081] It is preferable that such a conductive material be included in an amount of 0.1 to 10 weight percent of the total weight of the negative electrode active material layer, and more preferable that it be included in an amount of 1 to 5 weight percent. If the content of the conductive material is less than 0.1 weight percent, a sufficient conductive network is not formed, which may lead to a decrease in the electrical conductivity of the electrode and an increase in internal resistance, thereby potentially degrading high-rate charge / discharge characteristics. Conversely, if the content of the conductive material exceeds 10 weight percent, the relative content of the silicon active material decreases, which may lower the energy density of the electrode, and there is a risk that the mechanical stability and cycle characteristics of the electrode may be degraded due to a decrease in electrode density and excessive void formation.
[0082] A binder is added to bond the silicon active material and the conductive material, improve adhesion to the negative electrode current collector, and maintain the structural stability of the electrode even with volume changes of the silicon-based active material occurring during the charging and discharging process. These binders include polyvinylidene fluoride (PVdF), poly(vinylidene fluoride-co-hexafluoropropylene) (PVdF-HFP), polyvinylidene chloride (PVDC), polybenzimidazole (PBI), polyimide (PI), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), polyurethane (PU), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), starch, hydroxypropyl cellulose (HPC), and regenerated cellulose. cellulose), polyvinylpyrrolidone (PVP), polytetrafluoroethylene (PTFE), polyethylene (PE), polypropylene (PP), polystyrene (PS), polymethyl methacrylate (PMMA), polyaniline (PANI), acrylonitrile-butadiene-styrene (ABS), phenolic resin, epoxy resin,It may include one or more selected from polyethylene terephthalate (PET), polyphenylene sulfide (PPS), and polyamideimide (PAI).
[0083] More preferably, the binder may include CMC and SBR, and the CMC and SBR may be included in a weight ratio of 1:1 to 1:3, more preferably in a weight ratio of 1:1.5 to 1:2.5. CMC provides excellent bonding strength with the silicon active material to improve the mechanical strength of the electrode, and SBR imparts elasticity and flexibility to effectively absorb the volume expansion and contraction of silicon that repeatedly occur during the charge-discharge process, thereby suppressing cracking, delamination, and detachment of the active material from the electrode. Therefore, when CMC and SBR are used together, the structural stability, adhesion, and long-term cycle characteristics of the electrode can be further improved compared to when they are used alone.
[0084] It is preferable that such a binder be included in an amount of 1 to 10 weight percent of the total weight of the negative electrode active material layer, and more preferable that it be included in an amount of 3 to 6 weight percent. If the binder content is less than 1 weight percent, the bonding force between the silicon active material and the conductive material and the adhesion force between the negative electrode active material layer and the negative electrode current collector are not sufficiently secured, which may lead to detachment of the silicon active material, electrode cracking, or delamination, and the structural stability of the electrode may be reduced during repeated charge-discharge processes, thereby deteriorating cycle characteristics. Conversely, if the binder content exceeds 10 weight percent, the proportion of electrically inactive binder increases, which may reduce the relative content of the silicon active material, lower the electrical conductivity of the electrode, and cause an increase in internal resistance and a decrease in energy density. In addition, excessive binder may alter the pore structure of the electrode, thereby hindering the movement of lithium ions and degrading high-rate characteristics and long-term cycle characteristics.
[0086] Hereinafter, a lithium battery with improved interfacial stability and mechanical stability according to an embodiment of the present invention will be described with reference to the attached drawings.
[0087] FIG. 1 is a cross-sectional view showing a lithium battery with improved interfacial stability and mechanical stability according to an embodiment of the present invention.
[0088] Referring to FIG. 1, a lithium battery (500) with improved interfacial stability and mechanical stability according to an embodiment of the present invention comprises a positive electrode (100), a negative electrode (200), and a sulfide-based solid electrolyte (300).
[0090] The positive electrode (100) may include a positive electrode current collector and a positive electrode active material layer. As the positive electrode active material used in the positive electrode active material layer, a layered oxide-based active material, a spinel-based active material, an olivine-based active material, or a combination thereof, which are commonly used in the field of all-solid-state batteries (500), may be used. For example, the positive electrode active material may be LCO (LiCoO2) or NCM (LiNi x Co yMn z O2), NCA (LiNi x Co y Al z It may include one or more selected from O2), LMO (LiMn2O4), LFP (LiFePO4), etc., but is not limited thereto.
[0092] The negative electrode (200) is positioned to face the positive electrode (100). This negative electrode (200) may be a negative electrode for an all-solid-state battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention described above, and may include a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector. The negative electrode active material layer may include a silicon active material comprising micro silicon and a TiO2 protective coating layer formed to cover the surface of the silicon active material.
[0094] A sulfide-based solid electrolyte (300) is disposed between the positive electrode (100) and the negative electrode (200). This sulfide-based solid electrolyte (300) serves as a solid electrolyte layer that transmits lithium ions and may include a sulfide-based lithium ion conductive material. For example, the sulfide-based solid electrolyte (300) may include Li6PS5Cl, Li7P3S 11 , Li 10 GeP2S 12 It may include at least one of the combinations thereof, but is not limited thereto. Preferably, the sulfide-based solid electrolyte layer (300) may include Li6PS5Cl.
[0096] In the aforementioned negative electrode active material layer, the TiO2 protective coating layer is formed to cover the surface of the silicon active material in the form of a continuous film, and when the all-solid-state battery (500) is assembled, it is placed between the silicon active material and the sulfide-based solid electrolyte (300) to form a stable interface protective layer. Accordingly, direct contact between the silicon active material and the sulfide-based solid electrolyte (300) can be effectively blocked or reduced, thereby suppressing side reactions occurring at the interface.
[0097] In addition, it is preferable that the average film thickness of the TiO2 protective coating layer be 1 to 10 nm. If the average film thickness of the TiO2 protective coating layer is less than 1 nm, it is difficult to sufficiently protect the surface of the silicon active material, and there is a concern that the direct interfacial reaction between the silicon active material and the sulfide-based solid electrolyte (300) may not be sufficiently suppressed. Conversely, if the average film thickness of the TiO2 protective coating layer exceeds 10 nm, the TiO2 protective coating layer acts as a resistance layer for lithium ion movement, increasing the interfacial resistance of the electrode and potentially degrading the rate capability and output characteristics.
[0098] More preferably, the TiO2 protective coating layer may have an average film thickness of 3 to 5 nm. In this range, direct contact between the silicon active material and the sulfide-based solid electrolyte (300) can be effectively blocked while minimizing the increase in lithium ion mobility resistance. Accordingly, a TiO2 protective coating layer having an average film thickness of 3 to 5 nm is particularly desirable in terms of the balance of interfacial stability, mechanical stability, and electrochemical properties.
[0099] The TiO2 protective coating layer can cover more than 80% of the surface area of the silicon active material. Here, the coverage area can be confirmed using, for example, a transmission electron microscope (TEM), a scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), or X-ray photoelectron spectroscopy (XPS). If the coverage area of the TiO2 protective coating layer is less than 80% of the surface area of the silicon active material, the exposed area of the silicon active material increases, the direct contact area with the sulfide-based solid electrolyte (300) increases, and it may be difficult to sufficiently suppress interfacial side reactions and an increase in interfacial resistance. Conversely, if the TiO2 protective coating layer covers more than 80% of the surface area of the silicon active material, the direct contact area between the silicon active material and the sulfide-based solid electrolyte (300) can be effectively reduced, thereby improving interfacial stability.
[0100] This TiO2 protective coating layer can be formed via a sol-gel process. The sol-gel process utilizes the hydrolysis and condensation reactions of titanium alkoxide precursors to form a uniform TiO2 protective coating layer on the surface of a silicon active material. In particular, when using the sol-gel process, the TiO2 precursor can be uniformly distributed along the surface of micro-silicon particles, and a dense and continuous TiO2 protective coating layer can be formed through a subsequent heat treatment process.
[0101] The TiO2 protective coating layer is formed by a sol-gel process, thereby allowing the surface of the silicon active material to be coated in the form of a continuous film, unlike simple mechanical mixing or discontinuous particle attachment methods. Accordingly, the exposed area of the silicon active material is reduced, direct contact with the sulfide-based solid electrolyte (300) can be suppressed, and the increase in interfacial resistance during the charging and discharging process of the lithium battery (500) can be reduced.
[0102] Furthermore, TiO2 exhibits excellent chemical stability and can act as a relatively stable protective layer at the interface with sulfide-based solid electrolytes. Therefore, the TiO2 protective coating layer can suppress the decomposition of sulfide-based solid electrolytes during the charge-discharge process, mitigate interfacial degradation caused by volume changes of the silicon active material, and reduce the increase in interfacial resistance.
[0103] In this way, the electrode according to the present invention can block or reduce direct contact between the silicon active material and the sulfide-based solid electrolyte by forming a continuous film-shaped TiO2 protective coating layer on the surface of the silicon active material containing micro silicon. Accordingly, decomposition of the sulfide-based solid electrolyte and interfacial side reactions are suppressed, interfacial cracking and delamination caused by volume changes of the silicon active material during the charge-discharge process are mitigated, and interfacial stability, mechanical stability, long-term cycle characteristics, and rate capability characteristics of the all-solid-state battery can be improved.
[0104] As a result, the lithium battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention can simultaneously improve interfacial stability, mechanical stability, and electrochemical stability while maintaining the high energy density of the silicon anode, and can improve long-term charge / discharge cycle characteristics, capacity retention rate, and output characteristics. Furthermore, it can be effectively applied to electric vehicles (EVs), energy storage systems (ESS), aerospace, robots, and various next-generation energy storage systems that require high safety and high energy density.
[0106] The electrode and lithium battery with improved interfacial stability and mechanical stability according to the above-described embodiment of the present invention can provide a stable interfacial protective layer between the silicon active material and the sulfide-based solid electrolyte by forming a continuous film-type TiO2 protective coating layer on the surface of the silicon active material containing micro silicon. Accordingly, the electrode and lithium battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention can effectively block or reduce direct contact between the silicon active material and the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and side interfacial reactions, and can significantly improve chemical stability at the interface.
[0107] In addition, the electrode and lithium battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention can effectively relieve stress caused by the repeated volume expansion and contraction of the silicon active material during the charging and discharging process by having a TiO2 protective coating layer continuously cover the surface of the silicon active material. Accordingly, the electrode and lithium battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention can improve the mechanical stability of the electrode by suppressing cracking of the silicon active material, collapse of the active material layer, interfacial delamination, and contact loss, and can maintain stable interfacial contact even when charging and discharging are repeated for a long period.
[0108] In addition, the electrode and the lithium battery with improved interface stability and mechanical stability according to the embodiment of the present invention can improve charge / discharge efficiency and secure excellent rate capability by having a TiO₂ protective coating layer effectively suppress the increase in interface resistance between the silicon active material and the sulfide-based solid electrolyte and stably maintain the movement path of lithium ions. In addition, by reducing electrochemical degradation of the interface, long-term charge / discharge cycle life and capacity retention can be improved.
[0109] In addition, the electrode and the lithium battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention can minimize the resistance to lithium ion movement while securing sufficient protection for the silicon active material by strictly controlling the average film thickness of the TiO2 protective coating layer to 1 to 10 nm. Therefore, it is possible to simultaneously satisfy the interfacial protection effect and electrochemical performance, and simultaneously realize high energy density and excellent output characteristics.
[0110] In addition, the electrode and the lithium battery with improved interfacial stability and mechanical stability according to an embodiment of the present invention can effectively reduce local interfacial reactions and secure uniform interfacial characteristics across the entire electrode by uniformly covering more than 80% of the surface area of the silicon active material with a TiO2 protective coating layer. Accordingly, performance variations between cells can be reduced and stable battery characteristics can be maintained for a long period.
[0111] Furthermore, the electrode and lithium battery with improved interfacial and mechanical stability according to the embodiment of the present invention form a TiO2 protective coating layer using a sol-gel process, thereby enabling the formation of a uniform and dense protective coating layer on the surface of micro-silicon without the need for complex vacuum deposition equipment. Consequently, the manufacturing process exhibits excellent reproducibility and can reduce process costs, while also being easily applicable to large-area processes and mass production.
[0112] Accordingly, the electrode and the lithium battery with improved interfacial stability and mechanical stability according to the embodiment of the present invention can simultaneously improve interfacial stability, mechanical stability, long-term charge / discharge cycle characteristics, capacity retention rate, rate capability characteristics, and battery reliability, and can be effectively applied to electric vehicles (EVs), energy storage systems (ESS), and various next-generation all-solid-state battery fields requiring high energy density and high safety.
[0114] Hereinafter, a method for manufacturing an electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention will be described with reference to the attached drawings.
[0115] FIG. 2 is a process flowchart illustrating a method for manufacturing an electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention.
[0116] As illustrated in FIG. 2, the method for manufacturing an electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention includes a step of forming a TiO2 protective coating layer (S110), a step of forming a cathode slurry composition (S120), a step of forming a cathode slurry coating layer (S130), and a step of forming a cathode active material layer (S140).
[0118] TiO 2 Formation of a protective coating layer
[0119] In the step of forming a TiO2 protective coating layer (S110), a TiO2 protective coating layer is formed by a sol-gel process to cover the surface of a silicon active material containing micro silicon in the form of a continuous film.
[0120] Here, the sol-gel process is a process for forming a metal oxide thin film using the hydrolysis and condensation reactions of a titanium alkoxide precursor, and has the advantage of being able to form a uniform and dense coating layer even on the complex particle surfaces of silicon active materials.
[0121] More specifically, the step of forming a TiO2 protective coating layer (S110) may include the process of dispersing micro silicon in a dispersion solution containing anhydrous ethanol and an aqueous ammonia solution, the process of adding a titanium alkoxide precursor dropwise to the dispersion solution to induce hydrolysis and condensation reactions, the process of stirring after hydrolysis and condensation reactions to form a TiO2 protective coating layer on the surface of the micro silicon, the process of centrifuging, washing, and drying, and the process of heat treating the dried product.
[0122] First, in the dispersion process, micro silicon can be dispersed in a dispersion solution containing anhydrous ethanol and an aqueous ammonia solution. Anhydrous ethanol acts as a solvent to uniformly disperse the silicon active material and the titanium alkoxide precursor, while the aqueous ammonia solution can serve as a catalyst to promote the hydrolysis and condensation reactions of the titanium alkoxide.
[0123] At this time, dispersion can be performed using a stirrer, an orbital / rotating mixer, an ultrasonic disperser, or a combination thereof, and it is desirable that the silicon particles be uniformly dispersed without aggregation. Uniform dispersion has the effect of improving the uniformity of the subsequently formed TiO2 protective coating layer and reducing variations in coating thickness between particles.
[0124] In the precursor addition process, a titanium alkoxide precursor can be added dropwise to the dispersion solution. At this time, the titanium alkoxide precursor may be titanium tetraisopropoxide (TTIP), titanium tetrabutoxide (TTB), titanium tetraethoxide (TTE), or a combination thereof, and preferably, TTIP may be used.
[0125] It is preferable to add the titanium alkoxide precursor via a dropwise addition method. Applying the dropwise addition method can prevent the precursor from reacting excessively in local areas and allows for stable control of the hydrolysis rate.
[0126] Next, in the process of forming the TiO2 protective coating layer, the hydrolysis and condensation reactions can be sufficiently carried out by stirring for a certain period of time after the addition of the precursor is completed. The TiO2 precursor generated during this stirring process is adsorbed onto the surface of the silicon active material to form a continuous film-like TiO2 protective coating layer. Subsequently, the product is centrifuged to remove unreacted precursors, by-products are removed through washing, and then dried to obtain a silicon active material coated with TiO2. At this time, drying can be performed at room temperature or under heating conditions, and preferably for 12 to 36 hours. By performing sufficient drying, the solvent can be removed and the TiO2 precursor can be stabilized.
[0127] In this step, the TiO2 protective coating layer can be formed with an average film thickness of 1 to 10 nm, preferably 3 to 5 nm. Additionally, it is preferable that the TiO2 protective coating layer be formed to continuously cover at least 80% of the surface area of the silicon active material. Through such a structure, the exposed surface area of the silicon active material can be minimized, and direct contact with the sulfide-based solid electrolyte can be effectively suppressed.
[0128] Next, the dried coating particles can be heat-treated during the heat treatment process. At this time, the heat treatment is preferably performed in an inert gas atmosphere, and more preferably in an argon (Ar) atmosphere. The heat treatment temperature is preferably 600 to 700°C for 1 to 5 hours, and more preferably 640 to 680°C for 2 to 4 hours.
[0129] If the heat treatment temperature is below 600°C, the crystallization and densification of the TiO2 protective coating layer may not be sufficient, which may lead to a decrease in the structural stability of the coating layer. Additionally, if the bonding strength between the silicon active material and the TiO2 protective coating layer is not sufficiently secured, delamination or cracking of the coating layer may occur during the charge-discharge process, and there is a risk that the interface protection effect with the sulfide-based solid electrolyte may be reduced. Conversely, if the heat treatment temperature exceeds 700°C, excessive particle growth of the TiO2 protective coating layer may occur, leading to coarsening of the coating layer and a decrease in the uniformity of the coating layer. Furthermore, excessive oxidation of the surface of the silicon active material or inter-particle sintering may occur, which may degrade the lithium ion diffusion characteristics and lead to a decrease in the initial capacity and rate capability characteristics of the electrode.
[0130] In addition, if the heat treatment time is less than 1 hour, the crystallization and stabilization of the TiO2 protective coating layer are not sufficiently achieved, making it difficult to obtain the desired interfacial protection effect. Conversely, if the heat treatment time exceeds 5 hours, while the additional performance improvement effect is minimal, productivity may decrease due to increased manufacturing time, and there is a risk that structural changes in the silicon active material or coarsening of the coating layer may occur due to the long-term heat treatment.
[0131] Therefore, heat treatment can stabilize the structure of the TiO2 protective coating layer and improve the adhesion between the silicon active material and the TiO2 protective coating layer. In addition, heat treatment can increase the density of the TiO2 protective coating layer, thereby further enhancing the protective effect against sulfide-based solid electrolytes.
[0133] Formation of cathode slurry composition
[0134] In the step of forming the cathode slurry composition (S120), a silicon active material with a TiO2 protective coating layer, a conductive material, and a binder are mixed with a solvent to form a cathode slurry composition.
[0135] The conductive material forms a conductive network inside the electrode to facilitate the movement of electrons, while the binder secures the binding force between the active material and the current collector to maintain the stability of the electrode structure.
[0136] The solvent includes one or more selected from butanol, ethanol, isopropyl alcohol, propanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, polyethylene glycol, polypropylene glycol, and water.
[0137] In this step, mixing can be performed using an orbital / rotating mixer, a planetary mixer, or a high-speed stirrer, and it is preferable to perform the mixing at 500 to 2,500 rpm for 10 to 360 minutes, and more preferable to perform it at 1,000 to 2,000 rpm for 40 to 80 minutes. If the mixing speed is excessively low or the mixing time is short, the dispersibility of the slurry may be reduced, while conversely, excessive mixing may lead to unnecessary energy consumption and increased manufacturing costs.
[0139] Formation of cathode slurry coating layer
[0140] In the step of forming a cathode slurry coating layer (S130), a cathode slurry composition is coated onto a cathode current collector to form a cathode slurry coating layer.
[0141] In this step, various methods may be used for coating, such as doctor blade coating, spin coating, dipping coating, spray coating, roll coat coating, gravure printing, bar coat coating, die coating, comma coating, or a combination thereof.
[0142] Here, the cathode current collector may be made of one or more materials selected from copper (Cu), nickel (Ni), stainless steel, nickel-plated copper, copper alloy, etc. Such a cathode current collector may be a copper foil having a thickness of 5 to 20 μm, but is not limited thereto.
[0144] Formation of cathode active material layer
[0145] In the step of forming the negative electrode active material layer (S140), the negative electrode current collector on which the negative electrode slurry coating layer has been formed is dried to form the negative electrode active material layer.
[0146] In this step, drying may include a first drying process at a temperature of 70 to 90°C for 5 to 30 minutes under atmospheric pressure or reduced pressure, and a second drying process at a temperature of 75 to 95°C for 1 to 6 hours under vacuum.
[0147] At this time, the first drying step is intended to remove most of the solvent contained within the cathode slurry coating layer to stabilize the shape of the coating layer and ensure the uniformity of the coating layer. In addition, it prevents cracking, shrinkage, or peeling of the coating layer caused by rapid solvent evaporation, thereby enabling the formation of a uniform cathode active material layer.
[0148] The subsequent secondary drying is intended to further remove residual solvent within the negative electrode active material layer and stabilize the binding structure of the binder to improve adhesion between the silicon active material and the negative electrode current collector. In addition, by sufficiently removing moisture and volatile components within the negative electrode active material layer, side reactions during the subsequent battery assembly process can be suppressed, and electrochemical characteristics and long-term cycle characteristics can be improved.
[0149] If the first drying temperature is less than 70°C or the first drying time is less than 5 minutes, the solvent is not sufficiently removed, which may lead to a decrease in the uniformity of the coating layer and a decrease in the adhesion and mechanical strength of the negative active material layer. Conversely, if the first drying temperature exceeds 90°C or the first drying time exceeds 30 minutes, the solvent may evaporate excessively, leading to cracking of the coating layer, surface non-uniformity, or shrinkage of the active material layer.
[0150] In addition, if the secondary drying temperature is less than 75°C or the secondary drying time is less than 1 hour, residual solvent is not sufficiently removed, which may result in gas generation, increased interfacial resistance, or degraded electrochemical performance after battery assembly. Conversely, if the secondary drying temperature exceeds 95°C or the secondary drying time exceeds 6 hours, changes in the physical properties of the binder or structural changes in the negative electrode active material layer may occur, which may instead lead to a degradation of the electrode's mechanical stability and electrochemical properties.
[0151] After this drying step (S140), the negative active material layer may comprise 80 to 95 weight% of silicon active material with a TiO2 protective coating layer formed thereon, 0.1 to 10 weight% of conductive material, and 1 to 10 weight% of binder.
[0152] In the negative electrode active material layer, the TiO2 protective coating layer is formed to cover the surface of the silicon active material in the form of a continuous film, and when the all-solid-state battery is assembled, it is positioned between the silicon active material and the sulfide-based solid electrolyte to form a stable interface protection layer. Accordingly, direct contact between the silicon active material and the sulfide-based solid electrolyte can be effectively blocked or reduced, thereby suppressing side reactions occurring at the interface.
[0153] In addition, it is preferable that the average film thickness of the TiO2 protective coating layer be 1 to 10 nm. If the average film thickness of the TiO2 protective coating layer is less than 1 nm, it is difficult to sufficiently protect the surface of the silicon active material, and there is a concern that direct interfacial reactions between the silicon active material and the sulfide-based solid electrolyte may not be sufficiently suppressed. Conversely, if the average film thickness of the TiO2 protective coating layer exceeds 10 nm, the TiO2 protective coating layer acts as a resistance layer for lithium ion movement, increasing the interfacial resistance of the electrode and potentially degrading the rate capability and output characteristics.
[0154] More preferably, the TiO2 protective coating layer may have an average film thickness of 3 to 5 nm. Within this range, direct contact between the silicon active material and the sulfide-based solid electrolyte can be effectively blocked while minimizing the increase in lithium ion mobility resistance. Therefore, a TiO2 protective coating layer having an average film thickness of 3 to 5 nm is particularly desirable in terms of the balance of interfacial stability, mechanical stability, and electrochemical properties.
[0155] The TiO2 protective coating layer can cover more than 80% of the surface area of the silicon active material. Here, the coverage area can be confirmed using, for example, transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), or X-ray photoelectron spectroscopy (XPS). If the coverage area of the TiO2 protective coating layer is less than 80% of the surface area of the silicon active material, the exposed area of the silicon active material increases, leading to an increase in the direct contact area with the sulfide-based solid electrolyte, and it may be difficult to sufficiently suppress interfacial side reactions and an increase in interfacial resistance. Conversely, if the TiO2 protective coating layer covers more than 80% of the surface area of the silicon active material, the direct contact area between the silicon active material and the sulfide-based solid electrolyte can be effectively reduced, thereby improving interfacial stability.
[0156] This TiO2 protective coating layer can be formed via a sol-gel process. The sol-gel process utilizes the hydrolysis and condensation reactions of titanium alkoxide precursors to form a uniform TiO2 protective coating layer on the surface of a silicon active material. In particular, when using the sol-gel process, the TiO2 precursor can be uniformly distributed along the surface of micro-silicon particles, and a dense and continuous TiO2 protective coating layer can be formed through a subsequent heat treatment process.
[0157] Since the TiO2 protective coating layer is formed by a sol-gel process, the surface of the silicon active material can be coated in the form of a continuous film, unlike simple mechanical mixing or discontinuous particle attachment methods. Accordingly, the exposed surface area of the silicon active material is reduced, direct contact with the sulfide-based solid electrolyte can be suppressed, and the increase in interfacial resistance during the charging and discharging process of the all-solid-state battery can be reduced.
[0158] Furthermore, TiO2 exhibits excellent chemical stability and can act as a relatively stable protective layer at the interface with sulfide-based solid electrolytes. Therefore, the TiO2 protective coating layer can suppress the decomposition of sulfide-based solid electrolytes during the charge-discharge process, mitigate interfacial degradation caused by volume changes of the silicon active material, and reduce the increase in interfacial resistance.
[0159] In this way, the electrode according to the present invention can block or reduce direct contact between the silicon active material and the sulfide-based solid electrolyte by forming a continuous film-shaped TiO2 protective coating layer on the surface of the silicon active material containing micro silicon. Accordingly, decomposition of the sulfide-based solid electrolyte and interfacial side reactions are suppressed, interfacial cracking and delamination caused by volume changes of the silicon active material during the charge-discharge process are mitigated, and interfacial stability, mechanical stability, long-term cycle characteristics, and rate capability characteristics of the all-solid-state battery can be improved.
[0160] With this, the method for manufacturing an electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention may be concluded.
[0162] As described above, the electrode with improved interfacial stability and mechanical stability, the method for manufacturing the same, and the lithium battery according to the embodiment of the present invention can provide a stable interfacial protective layer between the silicon active material and the sulfide-based solid electrolyte by forming a continuous film-type TiO2 protective coating layer on the surface of the silicon active material containing micro silicon. Accordingly, the electrode with improved interfacial stability and mechanical stability, the method for manufacturing the same, and the lithium battery according to the embodiment of the present invention can effectively block or reduce direct contact between the silicon active material and the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and side interfacial reactions, and can significantly improve chemical stability at the interface.
[0163] Furthermore, the electrode with improved interfacial stability and mechanical stability according to the embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof can effectively relieve stress caused by the repeated volume expansion and contraction of the silicon active material during the charge and discharge process by having a TiO2 protective coating layer continuously coat the surface of the silicon active material. Accordingly, the electrode with improved interfacial stability and mechanical stability according to the embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof can improve the mechanical stability of the electrode by suppressing cracking of the silicon active material, collapse of the active material layer, interfacial delamination, and contact loss, and can maintain stable interfacial contact even when charging and discharging are repeated for a long period.
[0164] In addition, the electrode with improved interface stability and mechanical stability according to the embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof can improve charge / discharge efficiency and secure excellent rate capability by having a TiO₂ protective coating layer effectively suppress the increase in interface resistance between the silicon active material and the sulfide-based solid electrolyte and stably maintain the movement path of lithium ions. In addition, by reducing electrochemical degradation of the interface, long-term charge / discharge cycle life and capacity retention can be improved.
[0165] In addition, the electrode with improved interfacial stability and mechanical stability according to the embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof can minimize the resistance to lithium ion movement while securing sufficient protection for the silicon active material by strictly controlling the average film thickness of the TiO2 protective coating layer to 1 to 10 nm. Therefore, it is possible to simultaneously satisfy the interfacial protection effect and electrochemical performance, and simultaneously realize high energy density and excellent output characteristics.
[0166] In addition, the electrode with improved interfacial stability and mechanical stability according to an embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof can effectively reduce local interfacial reactions and secure uniform interfacial characteristics throughout the electrode by uniformly covering an area of 80% or more of the surface of the silicon active material with a TiO2 protective coating layer. Accordingly, performance variations between cells can be reduced and stable battery characteristics can be maintained for a long period.
[0167] Furthermore, the electrode with improved interfacial stability and mechanical stability according to the embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof form a TiO2 protective coating layer using a sol-gel process, thereby enabling the formation of a uniform and dense protective coating layer on the surface of micro-silicon without complex vacuum deposition equipment. Consequently, the manufacturing process exhibits excellent reproducibility and can reduce process costs, while also being easily applicable to large-area processes and mass production.
[0168] Accordingly, the electrode with improved interfacial stability and mechanical stability according to the embodiment of the present invention, the method for manufacturing the same, and the lithium battery thereof can simultaneously improve interfacial stability, mechanical stability, long-term charge / discharge cycle characteristics, capacity retention rate, rate capability characteristics, and battery reliability, and can be effectively applied to electric vehicles (EVs), energy storage systems (ESS), and various next-generation all-solid-state battery fields requiring high energy density and high safety.
[0170] Examples
[0171] Hereinafter, the structure and operation of the present invention will be explained in more detail through preferred embodiments of the present invention. However, these are presented as preferred examples of the present invention and should not be interpreted in any way as limiting the present invention.
[0172] Details not listed here can be sufficiently technically inferred by a person skilled in this field, so their explanation will be omitted.
[0174] 1. Battery manufacturing
[0176] Example 1
[0178] Si@TiO 2 Manufacturing of complex active materials
[0179] 5g of micro silicon (mSi) with an average diameter of 10㎛ was added to a dispersion solution containing anhydrous ethanol and an aqueous ammonia solution and uniformly dispersed.
[0180] Next, 4.77 g of titanium tetraisopropoxide (TTIP) was added dropwise to the dispersion solution to induce hydrolysis and condensation reactions.
[0181] Next, the mixed solution was continuously stirred to form a TiO₂ protective coating layer on the surface of the silicon particles.
[0182] Next, after the reaction was completed, the product was centrifuged and washed with ethanol to remove residual precursors and byproducts.
[0183] Next, the washed product was dried at room temperature (20℃) for 24 hours, and then heat-treated at a temperature of 650℃ for 3 hours in an argon (Ar) atmosphere to produce a Si@TiO2 composite active material with an average film thickness of 5 nm on the surface of the silicon active material.
[0185] Cathode manufacturing
[0186] A cathode slurry composition was prepared by uniformly mixing 95 wt% of the Si@TiO2 composite active material prepared by the above method, 1.0 wt% of the conductive material (super-P), and 4.0 wt% of the binder (polyvinylidene fluoride: PVdF) with NMP (N-Methyl-2-pyrrolidone) solvent using an orbital / rotating mixer at a speed of 1,500 rpm for 60 minutes.
[0187] Next, a cathode slurry composition was uniformly coated onto a copper (Cu) current collector using a doctor blade method to form a cathode slurry coating layer.
[0188] Next, the cathode slurry coating layer was first dried at 80°C for 10 minutes, and then secondarily dried in a vacuum oven at 80°C for 2 hours to form a cathode active material layer.
[0190] Battery manufacturing
[0191] After introducing 150 mg of sulfide-based solid electrolyte powder into a mold, a pellet-shaped sulfide-based solid electrolyte was prepared by applying pressure of 50 MPa for 2 minutes.
[0192] Next, the Si@TiO2 cathode prepared by the above method was placed on one side of the sulfide-based solid electrolyte, and the anode was placed on the other side of the sulfide-based solid electrolyte. At this time, LiNi was used as the anode active material for the anode. 0.8 Co 0.1 Mn 0.1 O2(NCM811) was used.
[0193] Next, the interfacial adhesion between the electrode and the solid electrolyte was secured by applying pressure of 394 MPa for 5 minutes, and then the battery was assembled while maintaining a pressure of 50.25 MPa with a torch wrench.
[0195] Example 2
[0196] A battery was manufactured in the same manner as in Example 1, except that the amount of TTIP added was increased to 6.26 g to form a Si@TiO2 composite active material with an average film thickness of 7 nm of the TiO2 protective coating layer.
[0198] Example 3
[0199] An all-solid-state battery was manufactured using the same method as in Example 1, except that the amount of TTIP added was reduced to 3.15 g to form a Si@TiO2 composite active material with an average film thickness of 2 nm of the TiO2 protective coating layer.
[0201] Comparative Example 1
[0202] A battery was manufactured in the same manner as in Example 1, except that the negative electrode was formed using only micro silicon as the negative electrode active material without forming a TiO2 protective coating layer.
[0204] Comparative Example 2
[0205] A battery was manufactured in the same manner as in Example 1, except that the amount of TTIP added was increased to 10.35 g to form a Si@TiO2 composite active material with an average film thickness of 15 nm of the TiO2 protective coating layer.
[0207] 2. Evaluation of physical properties
[0208] Table 1 shows the results of the physical property evaluation for batteries prepared according to Examples 1 to 3 and Comparative Examples 1 to 2.
[0210] [Table 1]
[0211]
[0212] As shown in Table 1, Comparative Example 1, which did not form a TiO2 protective coating layer, exhibited high interfacial resistance and a low capacity retention rate after long-term cycling. Additionally, Comparative Example 2, in which the thickness of the TiO2 protective coating layer was excessively formed at 15 nm, showed a tendency for the initial discharge capacity and capacity retention rate to decrease due to an increase in lithium ion mobility resistance, although some interfacial protection effect was secured.
[0213] On the other hand, Examples 1 to 3 all exhibited superior initial discharge capacity, initial Coulomb efficiency, and capacity retention rate compared to Comparative Examples 1 to 2, and in particular, Example 1, with an average film thickness of 5 nm, showed the most excellent reduction in interfacial resistance and long-term cycle characteristics.
[0215] 3. SEM and EDS Analysis
[0216] Figure 3 is an SEM image of the Si@TiO2 composite active material prepared according to Example 1, and Figures 4 and 5 are images showing the results of ESD mapping analysis for the Si@TiO2 composite active material prepared according to Example 1.
[0217] As can be seen from the SEM image shown in Fig. 3, the Si@TiO2 composite active material prepared according to Example 1 has micro silicon particles that maintain their original particle shape, and no particle fragmentation or severe aggregation was observed even after the sol-gel process. In addition, the surface of the particles maintains a relatively uniform outer structure, confirming that the TiO2 protective coating layer was stably formed.
[0218] In addition, as can be seen from the EDS mapping results shown in Figures 4 and 5, in the case of the Si@TiO2 composite active material prepared according to Example 1, it was confirmed that the Si component is distributed throughout the center of the particle, while the Ti component is uniformly distributed along the outer edge of the silicon particle. This means that the TiO2 protective coating layer is not formed locally in specific areas but continuously covers the entire surface of the silicon active material.
[0219] Therefore, it was confirmed that the TiO2 protective coating layer of the present invention can effectively cover a silicon surface in direct contact with a sulfide-based solid electrolyte and can sufficiently function as a protective layer to suppress side reactions occurring at the interface.
[0221] 4. XRD Analysis
[0222] Figure 6 is a graph showing the XRD analysis results for the Si@TiO2 composite active material prepared according to Example 1 and the micro silicon active material prepared according to Comparative Example 1.
[0223] As shown in Fig. 6, the Si@TiO2 composite active material prepared according to Example 1, like the micro silicon active material prepared according to Comparative Example 1, retained the silicon crystal peak while the TiO2 crystal phase was also confirmed.
[0224] This means that the crystallinity of the silicon active material was maintained even after the sol-gel process and heat treatment process, and at the same time, a TiO2 protective coating layer was successfully formed.
[0225] In addition, it was confirmed that the coating process does not damage the crystal structure of the silicon active material itself, as the major crystal peaks of silicon were not significantly reduced or shifted due to the formation of the TiO2 protective coating layer.
[0227] 5. Charge Transfer Resistance (Rct) Analysis
[0228] Figure 7 is a graph showing the measurement results of charge transfer resistance before cycling for batteries prepared according to Example 1 and Comparative Example 1, and Figure 8 is a graph showing the measurement results of charge transfer resistance after cycling for batteries prepared according to Example 1 and Comparative Example 1.
[0229] As shown in FIGS. 7 and 8, before the cycle, Example 1 showed a smaller semicircle diameter than Comparative Example 1.
[0230] This is believed to be the result of the TiO2 protective coating layer forming a stable interface between the silicon active material and the sulfide-based solid electrolyte, thereby reducing the initial interfacial resistance.
[0231] In addition, when the charge transfer resistance was measured again after performing a certain number of charge and discharge cycles, in Comparative Example 1, the semicircle diameter increased significantly and the interfacial resistance increased significantly, whereas in Example 1, the increase in the semicircle diameter was very small.
[0232] This is believed to be because the TiO2 protective coating layer effectively suppressed the decomposition of the sulfide-based solid electrolyte during the charge-discharge process and reduced interfacial degradation caused by volume changes of the silicon active material.
[0234] 6. Evaluation of Charge / Discharge Cycle Characteristics
[0235] Figure 9 is a graph showing the results of the charge-discharge cycle characteristics evaluation for batteries prepared according to Example 1 and Comparative Example 1.
[0236] As shown in Fig. 9, the battery manufactured according to Example 1 maintained its initial capacity stably and exhibited a high capacity retention rate even after long-term charging and discharging.
[0237] On the other hand, the battery manufactured according to Comparative Example 1 did not have a TiO2 protective coating layer, so as charging and discharging were repeated, interfacial reactions between the silicon active material and the sulfide-based solid electrolyte continued to occur, and consequently, the capacity decreased rapidly along with an increase in interfacial resistance.
[0239] Although the present invention has been described above with reference to embodiments, various changes and modifications can be made by those skilled in the art to which the present invention pertains. Such changes and modifications are considered to be within the scope of the present invention as long as they do not depart from the technical concept provided by the present invention. Accordingly, the scope of rights of the present invention should be determined by the claims set forth below. Explanation of the symbols
[0241] S110: Step for forming a TiO2 protective coating layer S120: Step of forming cathode slurry composition S130: Cathode slurry coating layer formation step S140: Cathode active material layer formation step 500 : Lithium battery 100 : Anode 200 : Cathode 300 : Sulfide-based solid electrolyte
Claims
Claim 1 An electrode with improved interfacial stability and mechanical stability, comprising: a negative electrode current collector; and a negative electrode active material layer formed on the negative electrode current collector; wherein the negative electrode active material layer comprises a silicon active material including micro silicon; and a TiO2 protective coating layer formed to cover the surface of the silicon active material; wherein the TiO2 protective coating layer is formed by a sol-gel process, and the TiO2 protective coating layer is formed such that the TiO2 is not discontinuously attached in the form of particles but forms a coating film continuously connected along the surface of the silicon active material, and is disposed between the silicon active material and a sulfide-based solid electrolyte, and wherein the TiO2 protective coating layer has an average film thickness of 3 to 5 nm and covers an area of at least 80% of the surface of the silicon active material. Claim 2 An electrode with improved interfacial stability and mechanical stability, characterized in that, in claim 1, the micro silicon has an average diameter of 1 to 20 μm. Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 An electrode with improved interfacial stability and mechanical stability, characterized in that, in claim 1, the TiO2 protective coating layer blocks direct contact with the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and reducing the increase in interfacial resistance. Claim 8 A lithium battery with improved interfacial stability and mechanical stability, comprising: a positive electrode; a negative electrode disposed opposite to the positive electrode; and a sulfide-based solid electrolyte disposed between the positive electrode and the negative electrode; wherein the negative electrode comprises a negative electrode current collector and a negative electrode active material layer formed on the negative electrode current collector, the negative electrode active material layer comprises a silicon active material including micro silicon and a TiO2 protective coating layer formed to cover the surface of the silicon active material, wherein the TiO2 protective coating layer is formed by a sol-gel process, and wherein the TiO2 protective coating layer is formed such that the TiO2 is not discontinuously attached in the form of particles but forms a coating film continuously connected along the surface of the silicon active material, wherein the coating film is disposed between the silicon active material and the sulfide-based solid electrolyte, and wherein the TiO2 protective coating layer has an average film thickness of 3 to 5 nm and covers an area of 80% or more of the surface of the silicon active material. Claim 9 A lithium battery with improved interfacial stability and mechanical stability, characterized in that, in claim 8, the micro silicon has an average diameter of 1 to 20 μm. Claim 10 delete Claim 11 delete Claim 12 delete Claim 13 delete Claim 14 A lithium battery with improved interfacial stability and mechanical stability, characterized in that, in claim 8, the TiO2 protective coating layer blocks direct contact with the sulfide-based solid electrolyte, thereby suppressing the decomposition of the sulfide-based solid electrolyte and reducing the increase in interfacial resistance. Claim 15 (a) a step of forming a TiO2 protective coating layer to cover the surface of a silicon active material containing micro silicon in the form of a continuous film by a sol-gel process; (b) a step of mixing the silicon active material with the TiO2 protective coating layer formed thereon, a conductive material, and a binder with a solvent to form a cathode slurry composition; (c) a step of coating the cathode slurry composition onto a cathode current collector to form a cathode slurry coating layer; and (d) a step of drying the cathode current collector on which the cathode slurry coating layer is formed to form a cathode active material layer; wherein the TiO2 protective coating layer is formed by a sol-gel process, and the TiO2 protective coating layer is formed such that the TiO2 is not discontinuously attached in the form of particles but forms a coating film continuously connected along the surface of the silicon active material, and is disposed between the silicon active material and a sulfide-based solid electrolyte, and the TiO2 protective coating layer has an average film thickness of 3 to 5 nm and covers an area of 80% or more of the surface of the silicon active material, characterized in that the electrode manufacturing method has improved interfacial stability and mechanical stability. Claim 16 In claim 15, the above step (a) comprises: (a-1) dispersing the micro silicon in a dispersion solution containing anhydrous ethanol and an aqueous ammonia solution; (a-2) adding a titanium alkoxide precursor dropwise to the dispersion solution to induce hydrolysis and condensation reactions; (a-3) stirring after the hydrolysis and condensation reactions to form a TiO₂ protective coating layer on the surface of the micro silicon, followed by centrifugation, washing, and drying; and (a-4) heat-treating the dried product; characterized in that it is a method for manufacturing an electrode with improved interfacial stability and mechanical stability. Claim 17 A method for manufacturing an electrode with improved interfacial stability and mechanical stability, characterized in that, in step (a-2) above, the titanium alkoxide precursor is titanium tetraisopropoxide (TTIP). Claim 18 delete Claim 19 delete Claim 20 A method for manufacturing an electrode with improved interfacial stability and mechanical stability, characterized in that, in step (a-3) above, the TiO2 protective coating layer covers an area of 80% or more of the surface of the silicon active material. Claim 21 A method for manufacturing an electrode with improved interfacial stability and mechanical stability, characterized in that, in step (a-4) above, the heat treatment is performed at 600 to 700°C for 1 to 5 hours under inert gas atmosphere conditions. Claim 22 A method for manufacturing an electrode with improved interfacial stability and mechanical stability, characterized in that, in step (d) above, the drying comprises: a step of primary drying for 5 to 30 minutes at a temperature of 70 to 90°C under atmospheric pressure or reduced pressure; and a step of secondary drying the primary dried product for 1 to 6 hours at a temperature of 75 to 95°C under vacuum atmosphere.
Citation Information
Patent Citations
Method of forming prelithiated silicon alloy electroactive material
CN112928242A
Silicon-based negative electrode material, preparation method thereof and battery
CN116722130A
Composite silicon-based negative electrode active material as well as preparation method and application thereof
CN120341228A
Carbon anode material for lithium secondary battery, method for preparing the same, and lithium secondary battery using the same
KR1020110100497A
Negative electrode for lithium ion secondary battery and method for producing the same
KR1020200118379A
